Desain Differentiated Instruction Pada Materi Statistika untuk Peserta Didik SMP: Alternatif Pembelajaran bagi Siswa Berbakat - Lita Lupita; Flavia Aurelia Hidajat (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This article presents a learning design for junior high school students using Defferentiated Instruction as a learning alternative for talented students on the topic of statistics. The development of learning in this flexible curriculum is carried out in such a way that a golden generation is born that meets the demands of the times. The birth of this golden generation can have a positive impact on the development of the Indonesian nation. A golden generation that is globally competitive can increase the confidence of the Indonesian people from a global perspective. On the other hand, the development of differentiated learning can provide opportunities to maximize the opportunities for learners to achieve their minimum abilities in accordance with the 2013 curriculum to achieve Indonesia's educational goals. Differentiated learning can fulfill the right to learn depending on the student's ability. We recommend that you use the results described in this article as an alternative to the learning process. In particular, it helps students solve problems related to statistical data.